Use of Dobutamine Stress Echocardiography for Periprocedural Evaluation of a Case of Critical Valvular Pulmonary Stenosis with Delayed Presentation - Barik, Ramachandra (J Cardiovasc Echogr, 2016)
We report a case illustrating a 39-year-old man with delayed presentation of severe pulmonary valve (PV) stenosis, clinical evidence of congestive right heart failure in the form of enlarged liver, raised jugular venous pressure, and anasarca without cyanosis. Echocardiography (echo) was used both for diagnosis and monitoring this patient as main tool. The contractile reserve of the right ventricle (RV) was evaluated by infusion of dobutamine and diuretic for 4 days before pulmonary balloon valvotomy. Both the tricuspid annular peak systolic excursion and diastolic (diastolic anterograde flow through PV) function of RV improved after percutaneous balloon pulmonary valvotomy. These improvements were clinically apparent by complete resolution of anasarca, pericardial effusion, and normalization albumin-globulin ratio. The periprocedural echo findings were quite unique in this illustration.